Biogenic Amines Detection by Chromatography and Sensor Methods: A Comparative Review - Muhammad Abdurrahman Munir; Khairiah Haji Badri; Lee Yook Heng (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2020)
Biogenic amines (BA) are chemistry compounds shaped by amino acids decarboxylation and exist in protein food and beverages. They are labelled toxic if consumed and some countries prohibit to consume them in high level especially histamine. Two major methods have been used and developed well such as chromatography methods and sensors methods. The common method applied for chromatography namely liquid chromatography (LC) and gas chromatography (GC) while for sensor methods such as optical, chemical and bio sensor. These methods have advantages and disadvantages. For chromatography methods, derivatization methods are required in order to improve their sensitivity and selectivity, nevertheless these methods are very expensive and time-consuming. During derivatization step, it needs more time and bear the risk of an only partial detection due to an incomplete derivatization. Furthermore, sensor methods exist to solve these issues, while they do not require derivatization step, generate a direct signal that can be interpreted by anyone, very fast and simple, yet they have disadvantages in several aspects such as sensitivity, accuracy and selectivity compared to chromatography methods. This review is based on studies about biogenic amines detection from the last decades until now and related to food and beverage samples. Although biogenic amines commonly found in protein-food for decades, new approaches and technical possibilities still required in order to increase the sensitivity, selectivity and accuracy of analytical methods to tackle the complexity by their matrices. The rationale of this study is also to provide data about the comparison of the analytical techniques between conventional and sensor methods. Furthermore, the various approaches of biogenic amines determination and the most applied analytical methods have been reviewed.